2017
DOI: 10.1136/bmjopen-2017-016091
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and depression among rural empty-nest elderly adults in Liuyang, China: a cross-sectional study

Abstract: ObjectiveTo compare loneliness, depressive symptoms and major depressive episodes between empty-nest and not-empty-nest older adults in rural areas of Liuyang city, Hunan, China.MethodsA cross-sectional multi-stage random cluster survey was conducted from November 2011 to April 2012 in Liuyang, China. A total of 839 rural older residents aged 60 or above completed the survey (response rate 97.6%). In line with the definition of empty nest, 25 participants who had no children were excluded from the study, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 28 publications
5
96
2
6
Order By: Relevance
“…A survey conducted by The Sixth National Census in 2010 showed that 13.3% of the total population was aged 60 and above in China. It indicates that the aging process gradually speeds up, meanwhile, the number of empty nest families is increasing [1]. In 2014, the survey of National Committee on Ageing determined that empty nesters accounted for 51.1% of the elderly in China [2].…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted by The Sixth National Census in 2010 showed that 13.3% of the total population was aged 60 and above in China. It indicates that the aging process gradually speeds up, meanwhile, the number of empty nest families is increasing [1]. In 2014, the survey of National Committee on Ageing determined that empty nesters accounted for 51.1% of the elderly in China [2].…”
Section: Introductionmentioning
confidence: 99%
“…China's elderly people have made up a large proportion of the whole [19], and the study on mental health of older adults is necessary. As reported, empty-nest families account for almost 25% of elderly household in China, and would increase to 90%by 2030 [20].As a special group, mental health and its related factors are very important problems for the empty-nesters. So, at present, the empty-nesters' mental health problem is one of the primary problems affecting China's social development [3].…”
Section: Discussionmentioning
confidence: 99%
“…Older adults who are experiencing the situation of the empty nest suffer from loneliness, physical and mental decline, and less life satisfaction compared to those who have regular contact with their children. 16 Low social support, low socio-economic status, divorce and widowhood were found to be predictors of loneliness and decreased life satisfaction. 17,18 Depressive symptoms were associated with education level/employment status, negative coping style, low support utilization, and economic status.…”
Section: Definition History and Theoretical Backgroundmentioning
confidence: 95%